Modified nanoparticle mediated IL-12 immunogene therapy for colon cancer. - Liu, Xiaoxiao; Gao, Xiang; Zheng, Songping; Wang, Bilan; Li, Yanyan; Zhao, Chanjuan; Muftuoglu, Yagmur; Chen, Song; Li, Ying; Yao, Haiyan; Sun, Hui; Mao, Qing; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2017)
For the past few years, immunotherapy has recently shown considerable clinical benefit in CRC therapy, and the application of immunologic therapies in cancer treatments continues to increase perennially. Interleukin-12, an ideal candidate for tumor immunotherapy, could activate both innate and adaptive immunities. In this study, we developed a novel gene delivery system with a self-assembly method by MPEG-PLA and DOTAP(DMP) with zeta-potential value of 38.5mV and size of 37.5nm. The supernatant of lymphocytes treated with supernatant from Ct26 transfected pIL12 with DMP could inhibit Ct26 cells growth ex vivo. Treatment of tumor-bearing mice with DMP-pIL12 complex has significantly inhibited tumor growth at both the subcutaneous and peritoneal model in vivo by inhibiting angiogenesis, promoting apoptosis and reducing proliferation. The IL-12 plasmid and DMP complex may be used to treat the colorectal cancer in clinical as a new drug. Copyright © 2017 Elsevier Inc. All rights reserved.
42 citations (Crossref) [2023-10-31] Place: United States Liu, Xiaoxiao. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China; Department of Medical Oncology, Cancer Center, State Key Laboratory of Biotherapy/Collaborative Innovation Center for Biotherapy, and West China Hospital, West China Medical School, Sichuan University, Chengdu, PR China. Gao, Xiang. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China. Electronic address: xiangxianggao2008@163.com. Zheng, Songping. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China. Wang, Bilan. Department of Pharmacy, West China Second University Hospital of Sichuan University, Chengdu, PR China. Li, Yanyan. Department of Radiation Oncology, Fudan University Shanghai Cancer Center, Fudan University, Shanghai, China. Zhao, Chanjuan. Department of Pharmacy, West China Second University Hospital of Sichuan University, Chengdu, PR China. Muftuoglu, Yagmur. Department of Pharmacology, Yale School of Medicine, Yale University, New Haven, CT, USA. Chen, Song. Department of Pharmacology, Yale School of Medicine, Yale University, New Haven, CT, USA. Li, Ying. Department of Pharmacology, Yale School of Medicine, Yale University, New Haven, CT, USA; Department of Clinical Laboratory, Second Affiliated Hospital of Dalian Medical University, Dalian, China. Yao, Haiyan. Southern Connecticut State University, New Haven, CT, United States. Sun, Hui. Department of Microbial Pathogenesis, Yale University School of Medicine, New Haven, CT, United States. Mao, Qing. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China. You, Chao. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China. Guo, Gang. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China. Wei, Yuquan. Department of Neurosurgery and Institute of Neurosurgery, State Key Laboratory of Biotherapy, West China Hospital, West China Medical School, Sichuan University and Collaborative Innovation Center for Biotherapy, Chengdu, PR China.
Keywords: *Angiogenesis Inhibitors/ad [Administration & Dosage]; *Colonic Neoplasms/th [Therapy]; *Gene Transfer Techniques; *Genetic Therapy; *Immunotherapy; *Interleukin-12/ad [Administration & Dosage]; *Nanoparticles/ch [Chemistry]; Adaptive immunity; Angiogenesis Inhibitors; Angiogenesis Inhibitors/ch [Chemistry]; Angiogenesis Inhibitors/pd [Pharmacology]; Animals; Apoptosis; Apoptosis/de [Drug Effects]; Article; Bagg albino mouse; Cell Proliferation; Cell Proliferation/de [Drug Effects]; Cell death; Colonic Neoplasms; Colonic Neoplasms/im [Immunology]; Colonic Neoplasms/me [Metabolism]; Colorectal cancer; Diseases; Drug delivery; Gene Transfer Techniques; Gene transfer; Genetic Therapy; Immunotherapy; Interleukin-12; Interleukin-12/ch [Chemistry]; Interleukin-12/ge [Genetics]; Interleukin-12/im [Immunology]; Mice; Mice; Inbred BALB C; Nanoparticles; Neovascularization; Pathologic; Neovascularization; Pathologic/dt [Drug Therapy]; Neovascularization; Pathologic/im [Immunology]; Polyesters; Polyesters/ch [Chemistry]; Polyethylene Glycols; Polyethylene Glycols/ch [Chemistry]; Potential values; Self assembly; Self-assembly method; Tumor Cells; Cultured; Tumor growth; Tumor immunotherapy; Tumors; adaptive immunity; angiogenesis inhibitor; animal; animal experiment; animal model; animal tissue; apoptosis; cancer immunotherapy; cell proliferation; cell viability; chemistry; colon carcinoma; colon tumor; controlled study; cytokine release; dept.bio; drug effect; enzyme linked immunosorbent assay; ex vivo study; flow cytometry; gamma interferon; gene therapy; gene transfer; genetics; immunology; immunotherapy; innate immunity; interleukin 12; macrogol derivative; messenger RNA; metabolism; methoxy poly(ethylene glycol)-poly(lactide); mouse; nanoparticle; neovascularization (pathology); nonhuman; oxaliplatin; phthalic acid dimethyl ester; polyester; reverse transcription polymerase chain reaction; tumor cell culture; tumor necrosis factor